Therapeutic Application of an Ag-Nanoparticle-PNIPAAm-Modified Eggshell Membrane Construct for Dermal Regeneration and Reconstruction - Emily Briggs; Rosemond A. Mensah; Kapil D. Patel; Nandin-Erdene Mandakhbayar; Nik San Sharifulden; Zalike Keskin Erdogan; Lady V. Barrios Silva; Kawther Salim; Hae-Won Kim; Linh T. B. Nguyen; David Y. S. Chau (MDPI AG, 2022)
Current therapeutic treatments for the repair and/or replacement of damaged skin following disease or traumatic injury is severely limited. The chicken eggshell membrane (ESM) is a unique material: its innate physical and mechanical characteristics offer optimal barrier properties and, as a naturally derived extract, it demonstrates inherent biocompatibility/biodegradability. To further enhance its therapeutic and clinical potential, the ESM can be modified with the thermo-responsive polymer, poly(N-isopropylacrylAmide) (PNIPAAm) as well as the incorporation of (drug-loaded) silver nanoparticles (AgNP); essentially, by a simple change in temperature, the release and delivery of the NP can be targeted and controlled. In this study, ESM samples were isolated using a decellularization protocol, and the physical and mechanical characteristics were profiled using SEM, FT-IR, DSC and DMA. PNIPAAm was successfully grafted to the ESM via amidation reactions and confirmed using FT-IR, which demonstrated the distinctive peaks associated with Amide A (3275 cm−1), Amide B (2970 cm−1), Amide I (1630 cm−1), Amide II (1535 cm−1), CH2, CH3 groups, and Amide III (1250 cm−1) peaks. Confirmation of the incorporation of AgNP onto the stratified membrane was confirmed visually with SEM, qualitatively using FT-IR and also via changes in absorbance at 380 nm using UV-Vis spectrophotometry during a controlled release study for 72 h. The biocompatibility and cytotoxicity of the novel constructs were assessed using human dermal fibroblast (HDFa) and mouse dermal fibroblast (L929) cells and standard cell culture assays. Metabolic activity assessment (i.e., MTS assay), LDH-release profiles and Live/Dead staining demonstrated good attachment and spreading to the samples, and high cell viability following 3 days of culture. Interestingly, longer-term viability (>5 days), the ESM-PNIPAAm and ESM-PNIPAAm (AgNP) samples showed a greater and sustained cell viability profile. In summary, the modified and enhanced ESM constructs were successfully prepared and characterized in terms of their physical and mechanical profiles. AgNP were successfully loaded into the construct and demonstrated a desirable release profile dependent on temperature modulation. Fibroblasts cultured on the extracted ESM samples and ESM-PNIPAAm demonstrated high biocompatibility in terms of high cell attachment, spreading, viability and proliferation rates. As such, this work summarizes the development of an enhanced ESM-based construct which may be exploited as a clinical/therapeutic wound dressing as well as a possible application as a novel biomaterial scaffold for drug development.